Effects of postbreeding gonadotropin treatments on conception rates of lactating dairy cows subjected to timed artificial insemination or embryo transfer in a tropical environment - Vasconcelos, José Luiz Moraes [UNESP]; Sa Filho, O. G. [UNESP]; Justolin, P. L. T. [UNESP]; Morelli, P. [UNESP]; Aragon, F. L.; Veras, M. B.; Soriano, S. (Elsevier B.V., 2011)
The objective of experiment 1 was to evaluate the effects of treatments with human chorionic gonadotropin (hCG) or GnRH 7 d after induced ovulation on reproductive performance of lactating dairy cows submitted to timed artificial insemination (TAI) or timed embryo transfer (TET). A total of 834 potential breedings were used from 661 lactating Holstein cows (37.3 +/- 0.3 kg of milk/d). Cows had ovulation synchronized and were assigned randomly to receive TAI on d 0 or TET on d 7. Within each group, cows were assigned randomly to receive on d 7 no additional treatment (control; n(TAI) = 156; n(TET) = 126), a 100 mu g i.m. injection of GnRH (n(TAI) = 155; n(TET) = 124), or a 2,500 TU i.m. injection of hCG (ITA = 151; n(TET) = 122). Postbreeding treatment affected the percentages of pregnant cows at TET on d 28 (control: 38.1%; GnRH: 52.4%; hCG: 45.1%) and on d 60 (control: 32.5%; GnRH: 41.1%; hCG: 38.5%), but postbreeding treatment did not affect percentages of pregnant cows at TAT on d 28 (control: 30.1%; GnRH: 32.2%; hCG: 32.4%) or on d 60 (control: 25.6%; GnRH: 27.1%; hCG: 29.8%). The objective of experiment 2 was to evaluate the effect of a treatment with GnRH 7 d after TET on reproductive performance of lactating dairy cows that received a previous GnRH treatment at TET. A total of 285 potential breedings were used from 257 lactating Holstein cows (35.1 +/- 0.8 kg of milk/d). Cows had ovulation synchronized and were assigned for TET on d 7. Immediately after TET, all cows were treated with a 100 mu g i.m. injection of GnRH. on d 14, cows were assigned randomly to receive (G7-14; n = 147) or not (G7; n = 138) an additional injection of GnRH. Pregnancy diagnosis were performed on d 28 and 60. The additional treatment with GnRH on d 14 did not affect the percentages of pregnant cows on d 28 (G7: 48.5%; G7-14: 42.9%) or on d 60 (G7: 39.8%; G7-14: 37.4%). In conclusion, treatment with GnRH or hCG 7 d after induced ovulation increased conception rates in lactating dairy cows submitted to TET, but not in cows submitted to TAI. Moreover, treatment with GnRH 7 d after TET did not enhance reproductive performance of lactating dairy cows that received a previous GnRH treatment at TET.
Keywords: artificial insemination; embryo transfer; gonadotropin-releasing hormone; human chorionic gonadotropin